Eye’s risk factors in age – related macular degeneration (AMD). Part I - Drobek-Słowik, Monika; Karczewicz, Danuta; Safrano, Krzysztof (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To evaluate the relationship between cataract, past cataract surgery and age-related macular degeneration (AMD). Material and methods: 281 eyes with AMD diagnosed with fundus fluorescein angiography were included to the study and divided into two groups: with dry (208) and exudative (73) type of AMD. 149 eyes without AMD were controls. We performed ophthalmological examination and questionnaire. We collected data regarding past cataract surgery, exposition to the sun, using of sunglasses and other. Results: Eyes with AMD were more likely to have cataract and nuclear sclerosis than controls. History of cataract surgery was significantly more frequent in group with exudative AMD compared to controls. Cataract (OR = 1.93), nuclear sclerosis (OR = 3.84) and past cataract surgery (OR = 2.32) were associated with increased risk of age-related macular degeneration in multivariate analyses adjusted for age. Conclusions: The concomitance of cataract (especially nuclear sclerosis) and age-related macular degeneration may support the theory of common pathogenesis of both pathologies. There is increased risk of exudative type of AMD in eyes after cataract surgery.